Human-felid conflict: a review of patterns and priorities worldwide - Inskip, Chloe; Zimmermann, Alexandra (Oryx, 2009)
Conflict between people and felids is one of the most urgent wild cat conservation issues worldwide, yet efforts to synthesize knowledge about these conflicts have been few. For management strategies to be effective a thorough understanding of the dynamics of human-felid conflicts is necessary. Here we present the results of a cross-species, systematic review of human-felid conflicts worldwide. Using a combination of literature review and geographical information system analyses, we provide a quantitative as well as qualitative assessment of patterns and determinants that are known to influence the severity of human-felid conflicts, and a geographical overview of the occurrence of conflict worldwide. We found evidence of conflict affecting over 75% of the world's felid species. The severity of conflict increases with felid body mass and is of greatest conservation significance to nine species: caracal, cheetah, Eurasian lynx, jaguar, leopard, lion, puma, snow leopard and tiger. We also reveal specific gaps in knowledge about human-felid conflicts, and required actions within this aspect of felid conservation. With only 31% of implemented management strategies having been evaluated scientifically, there is a need for greater and more rigorous evaluation and a wider dissemination of results. Also urgently required are standardized reporting techniques to reduce the current disparity in conflict reporting methods and facilitate resolution of patterns and trends in the scale of human-felid conflict worldwide. This review provides a basis both for further synthesis and for the coordination of human-felid conflict management among researchers, practitioners and organizations.